2019
DOI: 10.3389/fendo.2019.00407
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Recurrence for Multifocal Papillary Thyroid Microcarcinoma With Brafv600e Mutation: A Single Center Study of 1,207 Chinese Patients

Abstract: Background: The American Thyroid Association (ATA) guidelines risk stratify Braf v600e mutated multifocal papillary thyroid microcarcinoma (BMPTMC) into different recurrence risk groups by the extent of extrathyroidal extension (ETE). These findings and modifications for BMPTMC need to be verified in additional studies. Methods: A retrospective cohort study was conducted in BMPTMC patients who underwent total thyroidectomy (TT) and central lymph node di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Increasing evidence suggests that DTC patients with only gSMI have the same DFS as those with microscopic ETE (11). In our previous study, we also found that only four of 30 (13.3%) Braf-mutated thyroid papillary microcarcinoma patients with gSMI were diagnosed with recurrence (12). Accordingly, Shaha (13) suggested that a detailed distinction of gross ETE should be performed.…”
Section: Introductionmentioning
confidence: 61%
“…Increasing evidence suggests that DTC patients with only gSMI have the same DFS as those with microscopic ETE (11). In our previous study, we also found that only four of 30 (13.3%) Braf-mutated thyroid papillary microcarcinoma patients with gSMI were diagnosed with recurrence (12). Accordingly, Shaha (13) suggested that a detailed distinction of gross ETE should be performed.…”
Section: Introductionmentioning
confidence: 61%
“…Preoperative molecular testing results influencing the extent of surgery are very controversial. The mutation BRAFV600E is common in up to 60% of papillary thyroid carcinomas [10][11][12]. Some studies suggest that the presence of a BRAFV600E mutation predicts more aggressive behavior [12].…”
Section: Bethesda Staging On Fna Resultsmentioning
confidence: 99%
“…In contrast, TERT promotor mutations, alone or in combination with BRAFV600E mutations predict a high risk of recurrence or more aggressive disease course; thus, total thyroidectomy is recommended if these mutations are present [10,[12][13][14]. However, most of the studies addressing the impact of these genetic mutations relied on retrospective analysis of previously treated patients [10][11][12][13][14], and more prospective studies will be needed to elucidate a clear role of these genetic markers in the risk stratification and subsequent management of patients with differentiated thyroid cancer.…”
Section: Bethesda Staging On Fna Resultsmentioning
confidence: 99%
“…Husniye et al demonstrated that the presence of HT has no effect on ultrasonography features, fine‐needle aspiration biopsy outcomes, or histological findings of PTC lesions but is negatively associated with aggressive histopathological behaviour in PTMC 66 . Additionally, Xue et al 67 suggest that HT is protective against recurrence. However, Yin et al 68 show that HT is independently and positively linked to LNM in female PTMC patients aged <55 years.…”
Section: Discussionmentioning
confidence: 99%